Electrical Excitability of the Facial Muscles in Cleft Lip & Palate Cases - S. K. Bhatnagar; R. Chandra; R. N. Sharma; B. Dayal (Indian Journal of Plastic Surgery, 1978)
The present study show that the excitability of the orbicularis oris muscle on the cleft side was low as compared to the non cleft side, and as deformity was increasing from group 1-1/3 to group II a higher intensity of current was required to get minimal muscular contraction.